Facile Synthesis of Cyanoarenes from Quinones by Reductive Aromatization of Cyanohydrin Intermediates - Glöcklhofer, Florian; Lunzer, Markus; Fröhlich, Johannes (Synlett, 2015)
A novel synthesis of cyanoarenes from quinones by using PCl3 as the reagent for reductive aromatization of cyanohydrin intermediates is reported. In situ IR spectroscopic measurements were conducted to monitor the reactions and to develop a convenient one-pot protocol. 1,4-Dicyanobenzene and 9,10-dicyanoanthracene were prepared by the new procedure.
Keywords: arenes; cyanohydrins; nitriles; quinones; reduction